2013
DOI: 10.1186/1472-6963-13-530
|View full text |Cite
|
Sign up to set email alerts
|

Can the theoretical domains framework account for the implementation of clinical quality interventions?

Abstract: BackgroundThe health care quality improvement movement is a complex enterprise. Implementing clinical quality initiatives requires attitude and behaviour change on the part of clinicians, but this has proven to be difficult. In an attempt to solve this kind of behavioural challenge, the theoretical domains framework (TDF) has been developed. The TDF consists of 14 domains from psychological and organisational theory said to influence behaviour change. No systematic research has been conducted into the ways in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 70 publications
(85 reference statements)
2
58
0
1
Order By: Relevance
“…The greater the GPs’ perceived role, the more likely they were to report using exercise. This finding is not novel, previously, Lipworth et at identified that interventions were more likely to be adopted if they were perceived to be aligned with the HCPs’ role [49]. Linked to perceptions about role, is moral norm (i.e.…”
Section: Discussionmentioning
confidence: 61%
“…The greater the GPs’ perceived role, the more likely they were to report using exercise. This finding is not novel, previously, Lipworth et at identified that interventions were more likely to be adopted if they were perceived to be aligned with the HCPs’ role [49]. Linked to perceptions about role, is moral norm (i.e.…”
Section: Discussionmentioning
confidence: 61%
“…Individual barriers were tabulated by domain. To increase reliability of the assignment of barriers to a relevant TDF domain, a second coder (NT) with extensive experience using the TDF [40, 44, 45, 59] independently coded a sample of data segments until we were confident that there was agreement (approx. 9% of coded data).…”
Section: Methodsmentioning
confidence: 99%
“…The TDF has been used in a number of healthcare settings to study implementation and more specifically assist in the development of implementation interventions [16]. The TDF has also been used as a coding framework for the analysis of barriers in systematic reviews [2022]. In one study the TDF allowed the researchers to explore, explain and potentially target, using sophisticated behaviour change interventions, complex relationships, for example, limited “knowledge” appeared to influence healthcare professional’s ‘emotions’ [21].…”
Section: Introductionmentioning
confidence: 99%